The Proterozoic Nagssugtoqidian mobile belt of southeast Greenland: A link between the eastern Canadian and Baltic shields - Bridgewater, D.; Austrheim, H.; Hansen, B.; Mengel, F.; Pederson, S.; Winter, J. (Geoscience Canada)

(untitled) (The Geological Association of Canada, 1990)
Summary The Nagssugtoqidian mobile belt Is a ca. 300km wide Proterozoic tectonic zone, extending across Greenland, in which Archean basement rocks have been tectonically reworked and subjected to high-grade metamorphism. It is regarded as part of an originally continuous orogenic belt (Figure 1) which included the Tomgat Orogen of Labrador (Korstgard et al.. 1987) and the thrustbelts of Northern Norway and the Kola peninsula (Marker, 1988). All the segments are dominated by thrust tectonics and pressures up to 12 kb. In North Norway and West Greenland, juvenile Proterozoic sialic crustformed in association with sutures within the mobile belt. In East Greenland, Juvenile Prot-erozoic magmas are represented by basic intrusions emplaced into Archean continental crust. The location of the East Greenland section of the mobile belt is thought to have been controlled by pre-existing Late Archeanand very early Proterozoic structures.